USB SECURITY CAMERA - MOHD MAHDZIR, ZAIM (Universiti Teknologi Petronas, 2005)
USB Security Camera is a new way for a cheaper and convenient security system. The objective of this project is to develop a software that can recognizes more than one USB cameras connected to a single computer and streams each camera's output simultaneously or alternately to a computer's monitor. The software was written in Visual Basic 6.0 so that it is compatible with Windows platform. The main features of the application developed are automatic picture snap, motion detector and can support any USB camera. Motion detection features is a useful features in a place where there should be no movement. Unfortunately, the main aim which is to develop software that can detect more than one camera has failed. The software is not working as planned.